Three‐Dimensional Surface‐Based Analysis of Cartilage MRI Data in Knee Osteoarthritis: Validation and Initial Clinical Application. Issue 4 (24th May 2020) - MacKay, James W.; Kaggie, Joshua D.; Treece, Graham M.; McDonnell, Stephen M.; Khan, Wasim; Roberts, Alexandra R.; Janiczek, Robert L.; Graves, Martin J.; Turmezei, Tom D.; McCaskie, Andrew W.; Gilbert, Fiona J.
Abstract : Background: Traditional quantitative analysis of cartilage with MRI averages measurements (eg, thickness) across regions‐of‐interest (ROIs) which may reduce responsiveness. Purpose: To validate and describe clinical application of a semiautomated surface‐based method for analyzing cartilage relaxation times ("composition") and morphology on MRI, 3D cartilage surface mapping (3D‐CaSM). Study Type: Validation study in cadaveric knees and prospective observational (cohort) study in human participants. Population: Four cadaveric knees and 14 participants aged 40–60 with mild–moderate knee osteoarthritis (OA) and 6 age‐matched healthy volunteers, imaged at baseline, 1, and 6 months. Field Strength/Sequence: 3D spoiled gradient echo, T1 rho/T2 magnetization‐prepared 3D fast spin echo for mapping of T1 rho/T2 relaxation times and delayed gadolinium enhanced MRI of cartilage (dGEMRIC) using variable flip angle T1 relaxation time mapping at 3T. Assessment: 3D‐CaSM was validated against high‐resolution peripheral quantitative computed tomography (HRpQCT) in cadaveric knees, with comparison to expert manual segmentation. The clinical study assessed test–retest repeatability and sensitivity to change over 6 months for cartilage thickness and relaxation times. Statistical Tests: Bland–Altman analysis was performed for the validation study and evaluation of test–retest repeatability. Six‐month changes were assessed via calculation of the percentage of each cartilage surface affected by areas of significant change (%SC), defined using thresholds based on area and smallest detectable difference (SDD). Results: Bias and precision (0.06 ± 0.25 mm) of 3D‐CaSM against reference HRpQCT data were comparable to expert manual segmentation (−0.13 ± 0.26 mm). 3D‐CaSM demonstrated significant (>SDD) 6‐month changes in cartilage thickness and relaxation times in both OA participants and healthy controls. The parameter demonstrating the greatest 6‐month change was T2 relaxation time (OA median %SC [IQR] = 8.8% [5.5 to 12.6]). Data Conclusion: This study demonstrates the construct validity and potential clinical utility of 3D‐CaSM, which may offer advantages to conventional ROI‐based methods. Level of Evidence: 2. Technical Efficacy Stage: 2. J. Magn. Reson. Imaging 2020;52:1139–1151.